Engineering platinum-cobalt nano-alloys in porous nitrogen-doped carbon nanotubes for highly efficient electrocatalytic hydrogen evolution - Zhang, Song Lin (2021)
Highly efficient electrocatalysts are essential for the production of green hydrogen from water electrolysis. Herein, a metal-organic framework-assisted pyrolysis-replacement-reorganization approach is developed to obtain ultrafine Pt-Co alloy nanoparticles (sub-10 nm) attached on the inner and outer shells of porous nitrogen-doped carbon nanotubes (NCNT) with closed ends. During the thermal reorganization, the migration of Pt-Co nano-alloys to both surfaces ensures the maximized exposure of active sites while maintaining the robust attachment to the porous carbon matrix. Density functional theory calculations suggest a nearly thermodynamically-neutral free energy of adsorption for hydrogen intermediates and diversified active sites induced by alloying, thus resulting in a great promotion in intrinsic activity towards the hydrogen evolution reaction (HER). Benefiting from the delicate structural design and compositional modulation, the optimized Pt3 Co@NCNT electrocatalyst manifests outstanding HER activity and superior stability in both acidic and alkaline media.